Attachment and parental bond: impact on psychopathology, mental health and quality of life of hemodialysis patients: a cross-sectional study - Concetta De Pasquale; Maria Luisa Pistorio; Massimiliano Veroux; Gabriella Sapienza; Alberto Florio; Zira Hichy; Burcin Ekser; Alessia Giaquinta; Pierfrancesco Veroux (BMC Psychology, 2023)
Abstract Background Attachment theory represents a reference model for understanding better how pre-existing personality factors can influence the coping with some chronic conditions. The onset of a chronic disease can represent a "threat" to the relationships between the subject and parental figures according to the type of bond that already exists. The aim of our study was to explore attachment styles in a sample of hemodialysis patients, hypothesizing that a secure attachment bond can constitute a protective factor for the quality of life and mental health in this type of patients. Design We used a cross-sectional design. Methods Fifty hemodialysis patients were given the following tests: Attachment Style Questionnaire (ASQ) to assess attachment styles, Parental Bonding Instrument (PBI) to assess parental bonding, Short Form Health Survey-36 (SF-36) for perceived quality of life and Middlesex Hospital Questionnaire (MHQ) to detect key psychological symptoms and relevant traits. Results The results showed that secure attachment style correlated with good general health (r = 0.339; p < 0.05), good mental health (r = 0.547; p < 0.001) and mental component scale (r = 0.373; p < 0.05) of SF-36. Secure attachment was also significantly associated with mental health (B = 1.104; p = .002) of the SF-36. Conclusions The results confirmed the positive role of a secure attachment style for adequate psychological health. Early identification of patients with dysfunctional attachment styles will make it possible to offer them targeted interventions to improve their ability to accept, adapt and manage the disease and to maintain adequate psychological well-being.